Simulation and Modeling Methodologies, Technologies and Applications 7th International Conference, SIMULTECH 2017 Madrid, Spain, July 26-28, 2017 Revised Selected Papers - Obaidat, Mohammad S.; Ören, Tuncer; Rango, Floriano De.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book highlights a set of selected, revised and extended papers from the 7th International Conference on Simulation and Modeling Methodologies, Technologies and Applications (SIMULTECH 2017), held in Madrid, Spain, on July 26 to 28, 2017. The conference brought together researchers, engineers and practitioners whose work involves methodologies in and applications of modeling and simulation. The papers showcased here represent the very best papers from the Conference, and report on a broad range of new and innovative solutions.
Keywords: Computational intelligence; Artificial intelligence; Computer simulation; Computational Intelligence; Artificial Intelligence; Computer Modelling